Boundary Element Analysis Mathematical Aspects and Applications - Schanz, Martin; Steinbach, Olaf (Lecture Notes in Applied and Computational Mechanics, 2007)
This volume contains eleven state of the art contributions on boundary integral equation and boundary element methods. Beside some historical and more analytical aspects in the formulation and analysis of boundary integral equations also modern fast boundary element methods are described and analyzed from a mathematical point of view. In addition, engineering and industrial applications of those methods are presented showing the ability of state of the art boundary element methods to solve challenging problems from different fields of applications. This book is addressed to researchers, graduate students and practitioners working on and using boundary element methods. All contributions also show the great achievements of interdisciplinary research between mathematicians and engineers, with direct applications in industry.